Pengaruh Tingkat Adopsi Teknologi, Intensitas Penggunaan Tiktok, Interaksi Sosial dan Promosi Digital terhadap Strategi Komunikasi Pemasaran Matchaboy di Tiktok - Rahel Valentina Carolyn; Basuki Nugroho (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Amid rapid digital transformation, marketing communication has shifted toward interactive social media platforms, yet empirical evidence in the F&B sector—particularly on TikTok—remains limited. This study aims to examine the influence of technology adoption, TikTok usage intensity, social interaction, and digital promotion on the effectiveness of marketing communication strategies for the MatchaBoy brand. A quantitative approach was employed using survey data collected from 105 Generation Z respondents who had been exposed to MatchaBoy’s TikTok content. Data were analyzed through multiple linear regression after passing validity, reliability, and classical assumption tests. The results indicate that, partially, technology adoption (p = 0.166), usage intensity (p = 0.788), and social interaction (p = 0.076) do not have a significant effect on marketing communication effectiveness. In contrast, digital promotion shows a positive and significant influence (? = 0.767; p < 0.001). Simultaneously, all variables significantly explain the model with an adjusted R² of 0.707, indicating that 70.7% of the variance in effectiveness is accounted for by the proposed factors. These findings highlight that the effectiveness of marketing communication on TikTok is driven primarily by the quality and relevance of promotional content rather than the level of technology use or interaction intensity.